2016
DOI: 10.1111/hcre.12099
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms, Behavioral Payment Programs, and Cooperative Behaviors: Toward a Theory of Financial Incentives in Normative Systems

Abstract: Descriptive and injunctive social norms communicated among groups are known to influence behavior, yet little is known about how they evolve over time and how financial incentives influence norms. This article tests hypotheses about the ways in which monetary incentives can disrupt normative impact while facilitating cooperative behavior. The results of a public goods experiment indicate that the presence of a financial incentive for behavior can reduce the impact of perceived descriptive norms on behavior, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…They found that collective norms predicted individual condom use and that this influence was further augmented by heightened interpersonal discussions around the topic. In the second study, Lapinski, Kerr, Zhao, and Shupp () operationalized collective norms as the aggregated prevalence of actual behaviors of group members across trials in an experiment. They manipulated the presence of a financial incentive and sorted participants based on initial cooperation levels, finding that both descriptive and collective norms about donating to a financial pool predicted individuals' own contributions.…”
Section: Collective Norms and Perceived Normsmentioning
confidence: 99%
“…They found that collective norms predicted individual condom use and that this influence was further augmented by heightened interpersonal discussions around the topic. In the second study, Lapinski, Kerr, Zhao, and Shupp () operationalized collective norms as the aggregated prevalence of actual behaviors of group members across trials in an experiment. They manipulated the presence of a financial incentive and sorted participants based on initial cooperation levels, finding that both descriptive and collective norms about donating to a financial pool predicted individuals' own contributions.…”
Section: Collective Norms and Perceived Normsmentioning
confidence: 99%
“…Lapinski et al [26] tested the FINS model by using a public goods experiment in a campus computer laboratory setting in the U.S. In a public goods experiment, subjects had to decide how much to contribute between a public account, which maximized the benefits to the group as a whole, and a private account, which maximizes their own personal gain.…”
Section: Tests Of the Fins Modelmentioning
confidence: 99%
“…We present a nontechnical summary of an interdisciplinary model that combines insights from economics and communication sciences to examine the interaction of financial incentives and social norms in PES and other behavioral payment programs. (A more technical treatment of the model, with implications for the communication sciences literature, can be found in [26].) Our model takes advantage of the much greater nuance with which the communication literature treats social norms than the economics and institutions literatures, which tend to dominate the academic discussion of PES.…”
Section: Introductionmentioning
confidence: 99%
“…Lapinski et al (2017) provide an interesting study about the influence of financial incentives on the public good game. Their study explores the long‐term effect of behavioral payment programs especially when the financial incentives are offered in a short term …”
Section: Introductionmentioning
confidence: 99%
“…6 A novel work by De et al (2017) involves cultural inertia and social norm change in an evolutionary game to explore the societies' sensitivity for coordination, which might lead to norm change. 7 Lapinski et al (2017) provide an interesting study about the influence of financial incentives on the public good game. Their study explores the long-term effect of behavioral payment programs especially when the financial incentives are offered in a short term.…”
Section: Introductionmentioning
confidence: 99%